ANALISIS TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN LOGARITMA MELALUI PERMAINAN PEMBELAJARAN TIC-TAC-LOG - Usep Kosasih (Universitas Samudra, 2022)
Students need to have critical thinking skills to find solutions to personal or social problems in their lives. Critical thinking ability is the ability to process to solve problems in the best way according to existing experience and facts. This research is descriptive qualitative research with the aim of describing students' ability to think critically through the tic-tac-log learning game. The research subjects were students of class X MIPA 2 on of the high schools in Bandung Regency in the academic year 2021/2022, totaling 31 students. The critical thinking ability instrument was developed from the critical thinking ability of Facione. The instrument is in the form of 3 questions describing critical thinking skills on logarithmic material, each question consisting of aspects of interpretation, analysis, and evaluation. The analysis was carried out on students' answers and categorized into 5 categories, namely very high, high, moderate, low, and very low. The results showed that the students' critical thinking ability was high.